Pengaruh Plasticine Art Therapy Terhadap Kemampuan Regulasi Emosi Anak Usia 5-6 Tahun - Ni Nyoman Mulya Purwati; Pupung Puspa Ardini; Yenti Juniarti (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
The provision of unengaging art therapy makes children less enthusiastic about participating in the learning process. The purpose of this study is to determine whether plasticine art therapy influences the emotional regulation ability of 5-6 year-old children. This research is a quantitative experimental study with a Pre-Experimental One Group Pretest-Posttest Design. The population of this study consisted of 14 children. The sample in this study was 14 children in class B. The results of this study showed that the Pre-test data obtained an average score of 18.21 with a standard deviation of 1.31. Meanwhile, the Post-test data obtained an average score of 28.21 with a standard deviation of 2.51. This indicates that the respondents sampled in this study achieved an average increase in test scores from the beginning to the end. The calculated t-value obtained was 12.315, with a critical t-table of 0.227. If the calculated t-value is greater than the critical t-table, it can be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This means that there is an influence of plasticine art therapy on the emotional regulation ability of 5-6 year-old children in Teratai Kindergarten, Huangobotu Village, Kabila Bone District, Bone Bolango Regency.